Characterization of Hemagglutinin Gene Fragment of H9N2 Avian Influenza Virus Isolated from Environmental Live Bird Market in the Greater Jakarta Area - N. R. Maharani; H. Susetya; M. H. Wibowo (Faculty of Animal Science, Bogor Agricultural University, 2022)
Virus H9N2 has become the most common subtype of low pathogenic avian influenza (LPAI) in poultry and shows the ability to infect humans. One of the important factors triggering the virus ​​pandemic is the live bird market (LBM). The virus acts as an internal gene donor in the other subtypes, such as H5N1, H5N2, H7N9, and H10N8, in poultry and humans. This study was conducted to detect the presence of the H9N2 virus and the molecular characteristics of the hemagglutinin gene fragment at the cleavage site, receptor binding site, antigenic site, and glycosylation site positions of the H9N2 subtype AI virus isolated from the LBM environment. This study used Disease Investigation Center Subang isolates from environmental samples of LBM in the Greater Jakarta area (DKI Jakarta, Bogor, Depok, Tangerang, and Bekasi) in 2019. Based on molecular detection using RT-PCR and RT-qPCR, it was found that avian influenza subtype H9N2 was detected. This indicates that LBM has the potential to be the source of the spread of the ​​H9N2 virus. The pattern of the amino acid cleavage site PSRSSR↓GLF indicates that the research sample belongs to the low pathogenic AI. The substitution of amino acids in the receptor binding site and antigenic site increases the specificity of non-human host recognition. The potential glycosylation site, with the NCS motif found in amino acid position 295-297, close to the receptor-binding site. Based on genetic analysis and phylogenetic topography, the virus is included in the CVI (China, Vietnam, Indonesia) lineage and subclade H9.4.2.5.